Innate immunity in acute HIV-1 infection - Borrow, P (2011)
Purpose of review: Acute HIV-1 infection (AHI) is composed of the eclipse phase, during which the transmitted virus struggles to avoid eradication and achieve amplification/spread; the expansion phase when virus disseminates and undergoes exponential replication associated with extensive CD4 T-cell destruction; and the containment phase when set-point levels of viremia and immune activation are established. The importance of interactions between HIV-1 and innate responses in determining events throughout AHI is increasingly recognized, and is reviewed here. Recent findings: During the eclipse phase, HIV-1 subverts dendritic cell functions to promote its replication at mucosal sites and employs multiple strategies to minimize control by type 1 interferons. Systemic virus dissemination is associated with widespread activation of innate responses which fuels HIV-1 replication. To minimize the protective effects of innate responses, HIV-1 resists control by natural killer cells and may impair innate regulation of adaptive responses. Innate responses remain chronically activated after HIV-1 containment which is thought to drive HIV-1 pathogenesis. Summary: Innate responses are pivotal determinants of events at all stages of AHI. Increased understanding of mechanisms involved in innate control of HIV-1 and pathways regulating innate activation during HIV-1 infection could facilitate development of novel approaches to combating this infection. © 2011 Wolters Kluwer Health | Lippincott Williams and Wilkins.